Víctor Andrés Belaunde (1882-1966) - de la Puente Candamo, José Agustín (Mercurio Peruano, 2016)
This exposition highlights in Víctor Andrés Belaunde not only his intellectual interests, but his human qualities; so they stress important moments in the life of Belaunde, including his birth in 1883, the year of the Treaty of Ancon. Under the shadow of defeat, the Peruvian nation remained alive and this vision on Peru as something to be done, an ideal is reflected in his life and thought. Two are the evils of the current crisis which deserve to be considered from the thought of Belaunde: individualism and abstention.